Effects of modified sweet potato starch edible coating incorporated with cumin essential oil on storage quality of 'early crisp'. (January 2022) - Oyom, William; Xu, Hengping; Liu, Zhitian; Long, Haitao; Li, Yongcai; Zhang, Zhong; Bi, Yang; Tahergorabi, Reza; Prusky, Dov
Abstract: In this study, an edible formulation consisting of modified sweet potato starch (MSPS) and cumin essential oil (CEO) was developed. The effectiveness of the coating on the physiochemical and sensory traits of 'early crisp' stored at 25 °C for 28 d was evaluated. The results showed that incorporation of 0.2–0.4% (v/v) CEO in modified sweet potato starch edible coatings significantly ( p<0.05 ) reduced rot lesion on infected pear caused by Alternaria alternata, in vivo and also delayed changes in fruit color, firmness, and chlorophyll degradation. Coating significantly suppressed the onset of climacteric rise in respiration and minimized the weight loss of the pears. The stomata densities in coated pear were well preserved. Overall, the antifungal edible coating improved the storage quality of the pears and maintained consumable and better sensory quality compared to uncoated samples. The results suggest that modified sweet potato starch enriched with 0.2–0.4% (v/v) cumin essential oil could be useful as a preservation method to address issues of postharvest losses, and agricultural sustainability in the future. Highlights: Modified sweet potato starch coating containing cumin essential oil was developed. Treatment with 0.2% and 0.4% (MSPS/CEO) retarded black spot rot in 'early crisp'. The stomata of 'early crisp' were preserved by coating with MSPS/CEO. Sensory properties of 'early crisp' were not affected by coating with MSPS/CEO. MSPS/CEO coating offered a novel formulation for improving the quality of pear fruits.